AUTHORITARIAN DEMOCRACY AND POLITICAL DEVELOPMENT IN NIGERIA, 2007 – 2023 (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
The examination of liberal democracy co-existing with competitive authoritarianism in Nigeria relies on Democratic Peace Theory that explains how democratic institutions based on shared institutional frameworks and democratic values ensure peaceful relations. According to the core premise of the Democratic Peace Theory, these regimes stabilize their position through electoral liberalization while providing a measure of satisfaction to the opposition. The research adopts Analytical Design with documentary analysis to collect historical data from tables and media documents using descriptive methods that combine inductive and deductive approaches. The method analyzes several research elements to investigate Nigeria's democratic transformation from 1999 to 2023 specifically targeting both electoral improvements and the absorption of political opposition. Findings reveal that the practice of competitive authoritarianism during the years 2007 under Yar’Adua and 2023 under Tinubu has brought about internal peace through its inclusion of opposition forces in governance by distributing important appointments throughout different political parties. The 2022 Electoral Act along with other electoral reforms expanded voter participation through a large registered voting base yet did not eliminate electoral fraud because authoritarian tendencies remain strong. The hybrid system maintains control through elite balance to prevent anarchic conditions whereas Buhari demonstrated a complete lack of democratic practice during his eight years by rejecting all opposition and using brute military experience to exert force. The study recommends the modification of Nigeria’s political/democratic structure to make citizen needs more important than preserving the current regime. A national unity government which includes required opposition participation through designated positions would weaken competitive authoritarianism therefore strengthening authentic democratic societal institutions. The increased number of democracies worldwide since 1975 (from 44 to more than 150 by 2004) does not resolve Nigeria's challenges in creating a democratic system that integrates Western ideals with African communal values because of its complex cultural situation.